Undergraduate physiotherapy students’ performance in theoretical and practical examinations: A correlational case study in the UAE - Ramakrishnan, Senthilnathan (2019)
The study aimed at finding the correlation between the theoretical and the practical examinations marks of first year physiotherapy students and explore the possible contributory factors for any differences in exam performances. Mixed approach was used and correlation was analysed using Microsoft excel 2013 and interviews were employed to explore the factors associated with good or poor performances in the written and objective structured clinical examinations. There were no significant differences in the scores of theory and practical exams for the whole participants as the means of the former (40.05) and later (40.03) were nearly equal and the r value (0.672) indicated moderate positive correlation but individual differences in performances between the written and objective structured clinical examination noticed. Students and lecturers were interviewed and the qualitative data analysis identified factors associated with assessment methods, instructional strategies and learning styles were contributing for good and poor performances in the theoretical and practical examinations.